Plan4Blue Scenarios for Blue Growth: Qualitative analysis based on expert opinions - Riitta Pöntynen; Anne Erkkilä-Välimäki; Tua Nylén; Riku Varjopuro; Hanna Nieminen; Anu Lähteenmäki-Uutela; Tuomas Pohjola; Hanna Uusitalo; Janne Törrönen; Merle Kuris; Harri Tolvanen; Anneliis Peterson; et al. (Suomen ympäristökeskus, 2025)
Plan4Blue scenario process has a strong participatory element that is implemented by Delphi study and workshops. The scenario process adds qualitative information from Delphi rounds and workshops and leads to analysis on possibilities, also via identifying existing synergies or conflicts between blue economy sectors. In the first phase of the Plan4Blue scenario building, the aim was to look at possibilities and probabilities in order to create the draft future images. The analysis contained all blue economy sectors, in order to identify the important ones in terms of future development. In the second phase, selected blue economy sectors were focused on, based to the results of first rounds of Delphi, and to the results of economic analysis in WP T1. This deliverable present the finalized alternative scenarios for Blue Growth, including futures tables, futures images, and possible pathways leading to the alternative scenarios. They have been created based to the results of the Delphi rounds carried out in 2017 and 2018, and scenario workshops in Helsinki 2017 and Tallinn 2018. Links to deliverables on current status of blue economic business sectors and development trends of key sectors, and sector strategies will be done.
This deliverable combines the closely interlinked activity delivery reports:
D.T1.4.1 The first report on feedback and views of crossboundary and multisector expert panel
D.T1.5.1 Report of the first cross-border multilevel workshop, including first set of scenarios
D.T1.9.1 Second report of the Delphi-panel: report of the views of the experts
D.T1.10.1 Report of the second cross-border multilevel workshop; including final scenarios
D.T1.11.1 Final report of expert panel work
The maps produced as part of the process are presented in WP3 Deliverable D. T3.6.1 Maps visualizing first versions of blue growth scenarios (Roose et al. 2017).